KINERJA USAHA PETERNAKAN DAN PEMASARAN LEBAH MADU KELULUT (Apis trigona) PADA USAHA ARMEINA BENHIL DI DESA BENTENG HILIR KECAMATAN MEMPURA KABUPATEN SIAK - Meli Darmawati Halawa; Sisca Vaulina (UIR Press, 2024)
Kelulut bees represent a type of honeybee that can be farmed, presenting promising business opportunities and a significant market potential. This research aims to examine the profiles of entrepreneurs and their businesses, assess business performance (including cultivation techniques, expenses, production, income, efficiency, and break-even point), and analyze the marketing strategies for kelulut honey in Benteng Hilir Village, Mempura District, Siak Regency. Respondents were chosen using a census approach, and the data were analyzed both qualitatively and quantitatively. The findings indicate that: (1) the average age of the entrepreneurs is 43, with most holding a bachelor’s degree, possessing six years of business experience, and employing five staff. The business was initiated in 2016 and has partnered with PT. BKTJ since 2017, operating as a small-scale enterprise with a capital investment of IDR 139 million. (2) Production reached 27 kg per cycle, with a net income of IDR 5,248,333.33, a return on capital ratio of 1.76, and a break-even point of 15.34 kg. (3) Marketing was operated through two main channels: direct sales to consumers and sold through collectors and retailers, with direct marketing proving to be more cost-effective. Overall, this business has demonstrated profitability and holds significant potential for further development.